Responsibilitas Pelayanan Imunisasi Di Puskesmas Passitallu Dalam Perspektif Good Executive Governance Kabupaten Kepulauan - Alimuddin, Alimuddin; Razak, Andi Rosdianti; Parawu, Hafiz Elfiansyah (Universitas Muhammadiyah Makassar, 2021)
This study purposed to describe the Responsibility of Immunization Services at Passitallu Public Health Center in the Perspective of Good Executive Governance in Selayar Islands Regency. The research approach used descriptive qualitative. Data collection techniques through observation, interviews, and documentation. Informants in this study were 8 people who were selected purposively. The data analysis technique used interactive miles model. The results of this study indicated that the responsibility for immunization services at the Passitallu Public Health Center in the perspective of Good Executive Governance through 3 stages, the first was having commitment to carry out responsibility and authority by having their respective responsibilities and the main duties and functions of each member in the health center in immunization services, the second was having a HR management policy. (Human resources) Management was carried out with each member given the responsibility in each village to carry out immunizations in each village, and the third was having a policy of managing facilities and infrastructure that is adequate in terms of immunization equipment.Keywords: Responsibility for Immunization Services at Public Health Center